The transition of China to sustainable growth: Implications for the global economy and the euro area - Alistair Dieppe; Robert Gilhooly; Jenny Han; Iikka Korhonen; David Lodge (European Central Bank (ECB), 2018)
China's rise has been the economic success story of the past four decades but economic growth has been slowing and domestic imbalances have widened. This paper analyses the recent evolution of China's imbalances, the risks they pose to the economic outlook and the potential impact of a transition to sustainable growth in China on the global and euro area economies. The paper documents China's heavy reliance on investment and credit as drivers of growth, which has created vulnerabilities in a number of sectors and has been accompanied by increased complexity and leverage in the financial system. China retains some buffers, including policy space, to cushion against adverse shocks for the time being, but additional structural reforms would facilitate a shift of China's economy onto a sustainable and strong growth trajectory in the medium term. China's size, trade openness, dominant position as consumer of commodities and growing financial integration mean that its transition to sustainable growth is crucial for the global economic outlook. Simulation analysis using global macro models suggests that the spillovers to the euro area would be limited in the case of a modest slowdown in China's GDP growth, but significant in the case of a sharp downturn. Sensitivity analysis underscores that the spillovers are dependent on the strengths of the various transmission channels, as well as the policy reaction by central banks and governments.
Keywords: E21; E22; E27; F10; F47; O11; O53; 330; economic growth; rebalancing; China; imbalances; spillovers